Teknik Penerjemahan Tuturan Alih Kode dan Campur Kode dalam Film Aruna dan Lidahnya (2018) - Era Bawarti; Ria Herwandar (Universitas Al Azhar Indonesia, 2023)
This research is a translation-studies one discussing translation techniques used in Indonesian subtitle for English utterances and Indonesian utterances consisting English either words or expressions in the dialog of Aruna dan Lidahnya (2018) film. Analysis is done for utterances consisting code-switching and code-mixing. Methods used are descriptive-qualitative and library ones. Data are collected with content-analysis technique. Source text (ST) data are classified using code-switching and code-mixing classification. Target text (TT) data are classified using translation techniques by Molina and Albir (2002). Out of 72 data of bilingualism in use, 61.6% are code-mixing while 38.9% are code switching. Yet out of 37 utterances translated into Indonesian subtitle, 54.05% are code-switching while 45.95% are code-mixing. Out of 18 translation techniques proposed by Molina and Albir (2002), only 11 techniques used. Established equivalent is the most frequent techniques used, i.e. 23,1% out of 39 data in TT. The result also shows that all 11 translation techniques used are fit with the principle of subtitling according to Ho (2015). Keywords – translation, subtitle, code switching, code mixing, film Indonesia